Force-velocity relationship in paralympic powerlifting: two or multiple-point methods to determine a maximum repetition - Aidar, F. J.; Brito, C. J.; de Matos, D. G.; de Oliveira, L. A. S.; de Souza, R. F.; de Almeida-Neto, P. F.; de Araujo Tinoco Cabral, B. G.; Neiva, H. P.; Neto, F. R.; Reis, V. M.; Marinho, D. A.; Marques, M. C.; et al. (BMC Sports Science, Medicine and Rehabilitation, 2022)
Background Due to the absence of evidence in the literature on Paralympic Powerlifting the present study investigated various methods to assess bench press maximum repetition and the way each method influences the measurement of minimum velocity limit (MVT), load at zero velocity (LD0), and force-velocity (FV).